-8x+12y=-12

Add 8x to both sides of the equation.

12y=-12+8x

Divide each term in 12y=-12+8x by 12.

12y12=-1212+8×12

Cancel the common factor of 12.

Cancel the common factor.

12y12=-1212+8×12

Divide y by 1.

y=-1212+8×12

y=-1212+8×12

Simplify each term.

Divide -12 by 12.

y=-1+8×12

Cancel the common factor of 8 and 12.

Factor 4 out of 8x.

y=-1+4(2x)12

Cancel the common factors.

Factor 4 out of 12.

y=-1+4(2x)4(3)

Cancel the common factor.

y=-1+4(2x)4⋅3

Rewrite the expression.

y=-1+2×3

y=-1+2×3

y=-1+2×3

y=-1+2×3

y=-1+2×3

Solve for y -8x+12y=-12